Defect depth estimation in passive thermography using neural network paradigm - Heriansyah, Rudi; Syed Abu Bakar, Syed Abdul Rahman (2007)
Defect depth estimation from passive thermography data based on neural network paradigm is proposed. Three parameters have been found to be related with depth of the defect. Therefore, these parameters: the maximum temperature over the defective area (T-max), the temperature on the non-defective or sound area (T-so), and the average temperature (T-avg) of the inspected area have been used as input parameters to train multilayer perceptron neural networks. For verification of the proposed scheme, NN has been tested with trained and untrained data. The correct depth estimation is 100% for trained data and more than 98% for untrained data. The result shows a great potential of the proposed method for defect depth estimation by means of passive thermography.